(3TQM ebOeI cTa GdZWGAs - (3GdLfGMj, GdfLaj, cGTa GdZWGA, MSf Hf LYaQ Hf NVQ, J (B1262 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B.. (3Cfg bO GdJeSfj HYV GdCUMGH Cf CTQM ebOeI cTa GdZWGA GdeTJedI Ydi GdeWGdH GdCUhdjI TQMG efGSHG dgG aCLHJge deG SFdhG JGQcG ddJWhjd eMGaXG Ydi LGOI GdGNJUGQ djSgd JfGhdg hjYe faYg (B...s
(3BNQgG (B:s
.. (3hgPG cdg dJfHjg GdZGadjf Yf GdCUhd GdcdjI hEdG addabjg aj GdeSGFd GdLRFjI hGdebGeGJ GdabgjI JQGLjM dG JMUi hCfXGQ dG JSJbUi jYQagG ajg ehGQO Gdabg hef edGMXI GdCNHGQ hcdGe GdYdeGA GdCHQGQ (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\186s
(3gOjI GdYGQajf (B1\302s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs